The role of the informal and formal organisation in voice about concerns in healthcare: A qualitative interview study. (July 2021) - Wu, Frances; Dixon-Woods, Mary; Aveling, Emma-Louise; Campbell, Anne; Willars, Janet; Tarrant, Carolyn; Bates, David W.; Dankers, Christian; Mitchell, Imogen; Pronovost, Peter; Martin, Graham P.
Abstract: The importance of employee voice—speaking up and out about concerns—is widely recognised as fundamental to patient safety and quality of care. However, failures of voice continue to occur, often with disastrous consequences. In this article, we argue that the enduring sociological concepts of the informal organisation and formal organisation offer analytical purchase in understanding the causes of such problems and how they can be addressed. We report a qualitative study involving 165 interviews across three healthcare organisations in two high-income countries. Our analysis emphasises the interdependence of the formal and informal organisation. The formal organisation describes codified and formalised elements of structures, procedures and processes for the exercise of voice, but participants often found it frustrating, ambiguous, and poorly designed. The informal organisation—the informal practices, social connections, and methods for making decisions that are key to coordinating organisational activity—could facilitate voice through its capacity to help people to understand complex processes, make sense of their concerns, and frame them in ways likely to prompt an appropriate organisational response. Sometimes the informal organisation compensated for gaps, ambiguities and inconsistencies in formal policies and systems. At the same time, the informal organisation had a dark side, potentially subduing voice by creating informal hierarchies, prioritising social cohesion, and providing opportunities for retaliation. The formal and the informal organisation are not exclusive or independent: they interact with and mutually reinforce each other. Our findings have implications for efforts to improve culture and processes in relation to voice in healthcare organisations, pointing to the need to address deficits in the formal organisation, and to the potential of building on strengths in the informal organisation that are crucial in supporting voice. Highlights: Healthcare organisations often struggle to access and make use of employee voice. The concept of the 'informal organisation' helps to explain and address this issue. Some aspects of informal organisation may facilitate voice; others inhibit it. Informal and formal organisation interact with one another in complex ways. Interventions to improve voice should anticipate and account for these interactions.